Legal Policy Concept of the Republic of Kazakhstan until 2030: what laws in the sphere of domestic and foreign policy activities can be improved and adopted - Sarsembayev, M.A. (Bulletin of the Karaganda University “Law Series”, 2022)
This article is devoted to the analysis of the current laws of the Republic of Kazakhstan, which should be improved, as well as the justification of new Kazakh laws that should be developed and adopted within the framework of the concept of legal policy of the Republic of Kazakhstan until 2030. The research of the proposed topic of the scientific article is based on the legal logic and comparative legal analysis methods of the laws of Kazakhstan and a number of foreign countries, the method of scientific forecasting of new laws that should be adopted. The norms for improving the mechanisms for the implementation of human rights and freedoms based on the provisions of the concept of legal policy are proposed. The article proposes legislative and legal formalization of the processes of digitalization of the country’s economic sectors, justice processes,legal support for issues of foreign policy and foreign economic activity, taxation, combating economic and corruption crimes within the framework of the concept of legal policy and other conceptual documents of the republic.